Combined use of the integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) framework with other implementation frameworks: a systematic review - Sarah C. Hunter; Samantha Morgillo; Bo Kim; Anna Bergström; Anna Ehrenberg; Ann Catrine Eldh; Lars Wallin; Alison L. Kitson (Implementation Science Communications)
Abstract Background Appropriately and comprehensive applying implementation frameworks is one of the key challenges in implementation science resulting in increased use of multiple implementation frameworks within projects. This is particularly true for frameworks such as PARIHS/i-PARIHS. Therefore, this systematic review aimed to examine if and why the PARIHS/i-PARIHS framework has been applied in research with other implementation frameworks. Methods We searched six databases from 2016 (the year following i-PARIHS’ publication) to April 2024 and supplemented this with a citation search of the seminal i-PARIHS paper. We included studies that 1) were peer-reviewed with a protocol or empirical study design, 2) have applied the PARIHS or i-PARIHS framework for implementation planning, delivery, analysis, or evaluation and 3) also used at least one other implementation framework. Descriptive statistics were conducted to report on study characteristics and frequency for each implementation framework used with PARIHS/i-PARIHS. A qualitative, content analysis was used to analyse the answers to open-ended extraction questions. Results Thirty-six articles met criteria for inclusion and included 16 protocols and 20 empirical articles (twelve intervention and eight cross-sectional studies). Thirty-four of the studies used one additional implementation framework and two studies used two additional implementation frameworks. In total, nine implementation frameworks were applied with PARIHS/i-PARIHS, including: 1) RE-AIM, 2) CFIR, 3) NPT, 4) REP, 5) TDF, 6), DSF, 7) KTA, 8) Stetler’s Model, and 9) SIF. Thirty-four reported a rationale for using PARIHS/i-PARIHS and 34 reported a rationale for using the other implementation framework. Only eleven reported a rationale for using more than one implementation framework. Only three reported strengths of combining implementation frameworks. Conclusions Overall, this review identified that implementation researchers are using PARIHS/i-PARIHS in combination with other implementation frameworks and providing little to no rationale for why. Use of multiple implementation frameworks without detailed rationales compromises our ability to evaluate mechanisms of effectiveness. Implementation researchers and practitioners need to be more explicit about their framework selection, detailing the complementary strengths of the frameworks that are being used in combination, including why using one is not sufficient. Trial registration This systematic review was registered with PROSPERO: ID: 392147.